1987
DOI: 10.3382/ps.0661901
|View full text |Cite
|
Sign up to set email alerts
|

Selection for Resistance to Aflatoxin in Chickens

Abstract: Two populations of broiler chickens [Athens-Canadian (AC) and a commercial stock] were selected for resistance to aflatoxicosis by dosing chickens in each population with a single oral dose of aflatoxin, which resulted in 40 to 70% mortality. Chickens that did not receive aflatoxin served as the nonselected control groups. Birds surviving the aflatoxin challenge were used as breeders for subsequent generations. Rapid progress was made in the AC population for resistance to aflatoxin, but only moderate progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

1990
1990
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 6 publications
0
6
0
2
Order By: Relevance
“…A direct comparison cannot be made between mortality values resulting from the single oral dose of aflatoxin in the present study and the LD50 values reported for fifth generation progeny of the C and AR lines by Wyatt et al (1987), because those values were calculated from six different doses of aflatoxin administered to each line. However, mortality values of 63% and 30% for the C and AR lines, respectively, were obtained when fifth generation progeny were administered 12 mg of aflatoxin per kg of BW (Wyatt et al, 1987). From these data, it appears that there was a difference in the relative aflatoxin resistance between lines of the fifth and sixth generation progeny.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…A direct comparison cannot be made between mortality values resulting from the single oral dose of aflatoxin in the present study and the LD50 values reported for fifth generation progeny of the C and AR lines by Wyatt et al (1987), because those values were calculated from six different doses of aflatoxin administered to each line. However, mortality values of 63% and 30% for the C and AR lines, respectively, were obtained when fifth generation progeny were administered 12 mg of aflatoxin per kg of BW (Wyatt et al, 1987). From these data, it appears that there was a difference in the relative aflatoxin resistance between lines of the fifth and sixth generation progeny.…”
Section: Discussionmentioning
confidence: 91%
“…Chicks used in the present study were sixth generation progeny from lines of AC chickens selected for five generations for resistance to a single oral dose of aflatoxin (AR line) or maintained as an unselected control line (C line) as described by Wyatt et al (1987). Dayold chicks were placed in electrically heated batteries with raised wire floors under continuous illumination.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Selection for AFB1 resistant lines of chicken [291][292][293][294][295] and quail [296][297][298][299] has been investigated; however, selection studies have not been performed in the far more sensitive domestic turkey. Improvement in AFB1 resistance is highly dependent on starting population [299] and selection is most effective during AFB1 challenge since correlations of phenotypic measures like weight gain or blood parameters are most informative during exposure [291,292,298].…”
Section: Selection For Resistancementioning
confidence: 99%
“…Other authors, however, reported a lack of effect on growth rates on certain chicken lines fed 20 mg/kg aflatoxin and attributed this to a genetic variation in the resistance of chickens as a result of chronic exposure to aflatoxin (Lanza et al ., 1982;Wyatt et al ., 1987). It is therefore possible that because of continuous exposure of village chickens to aflatoxin they are bound to develop resistance, as suggested by our results.…”
Section: Discussionmentioning
confidence: 99%